Sanksi Pidana terhadap Kejahatan Pishing Menurut Hukum Pidana Indonesia - Putri Ramadhani Rangkuti; Muhammad Aldi Khoiri; Sumantri Ritonga; Putri Nabila Sitorus Pane (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study uses a qualitative method to examine the criminal sanctions against phishing crimes under Indonesian criminal law. Phishing is a form of cybercrime committed by deceiving victims into disclosing personal or confidential information such as identity data, bank accounts, or other sensitive details. In Indonesian criminal law, phishing is not explicitly mentioned, but it can be prosecuted under several articles of the Electronic Information and Transactions Law (Law No. 19 of 2016), particularly Articles 35 and 36, which regulate manipulative acts that cause harm to others. Offenders may face imprisonment of up to 12 years and/or fines of up to 12 billion rupiah. Additionally, offenders may be charged under the Indonesian Penal Code (KUHP) if their actions meet the elements of fraud or data theft. This study highlights the need for legal reform to be more responsive to the rapid advancement of digital technology. More specific regulations are needed to ensure legal certainty and provide adequate protection for victims of phishing crimes in Indonesia.